CHARACTERISTIC OF THE IODINE PROVISION OF THE CHILD ORGANISM AGAINST DIFFUSE NONTOXIC GOITER AND ITS EFFECT ON DENTAL PATHOLOGY - Годованець, О.І. (World of Medicine and Biology, 2015)
Worsening of iodine provision were observed in children with euthyroiden-induced enlargement of the thyroid gland, that can affect on metabolic processes in the child organism, and the dentoalveolar system in particular. It is proved by reliably worse rates of the intensity of affliction of the hard dental tissues and periodontal tissues in children suffering from diffuse nontoxic goiter.
Keywords: children; diffuse nontoxic goiter; dental diseases